KEDUDUKAN ISTRI NON MUSLIM TERHADAP HARTA BERSAMA DAN HARTA PENINGGALAN SUAMI DALAM PERKAWINAN BEDA AGAMA (ANALISIS PUTUSAN MAHKAMAH AGUNG NOMOR 16K/AG/2010) - RIZKI RIZKI (PREMISE LAW JURNAL, 2017)
Based on Article 2, paragraph 1 of Law on Marriage, it is impossible to get married with a person who has different religion because religion itself prohibits a mixed marriage. However, the existence of the Jurisprudence of the Supreme Court No. 1400/K/Pdt/1986, a mixed marriage can be registered. The registration causes the wife has the right for joint property and her late husband’s property. MUI in their advice explain that granting property to a person who has different religion should be in the form of hibah (grant), last will and testament, and gift. The panel of judges’ consideration the Supreme Court’s Ruling No. 16/K/AG/2010 is that a mixed marriage is registered so that the wife has a part of joint property. On the other hand, there is a mistake in implementing wasiat wajibah in the dispute of inheritance, viewed from some jurisprudences; the giving of wasiat wajibah to a non-Muslim implies that the receiver has the same right as a Muslim heir which is contrary to the Islamic law and does not fulfill the sense of justice.Keywords: Mixed Marriage; Joint Property; Late Husband’s Property